2021
DOI: 10.1080/21505594.2021.1903212
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of genes related to innate antifungal immunity in the absence of galectin-3

Abstract: Galectin-3 (Gal-3) is the most studied member of the animal galectin family, which comprises βgalactoside-binding lectins and participates in several cellular events. Its expression in cells involved in innate and adaptive immunity is related to anti-and proinflammatory functions, signaling an important role in inflammatory, infectious, and tumorigenesis processes. Mice deficient in Gal-3 exhibit important phenotypes, but it is unclear whether these phenotypes reflect an impairment of the functions of this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Our group demonstrated that the absence of Gal-3, under physiological conditions, promotes changes in the expression of genes involved in innate host immunity [ 13 ], however, we proposed to study the influence of Gal-3 on gene expression in fungal infections compared to the control animal (Gal-3 KO vs. WT). During experimental C. neoformans infection, Gal-3 absence promotes upregulation of chemokines ( ccl12 , cxcl9 and cxcl10 ) and ifn-ɣ in the lungs ( Table S2 and Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group demonstrated that the absence of Gal-3, under physiological conditions, promotes changes in the expression of genes involved in innate host immunity [ 13 ], however, we proposed to study the influence of Gal-3 on gene expression in fungal infections compared to the control animal (Gal-3 KO vs. WT). During experimental C. neoformans infection, Gal-3 absence promotes upregulation of chemokines ( ccl12 , cxcl9 and cxcl10 ) and ifn-ɣ in the lungs ( Table S2 and Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Galectin-3 plays an important role in the expression of genes related to innate immunity in the host. Its absence, under physiological conditions, promotes differentially modulated genes involved in the transcription of beta-glucan, mannose, and chitin-responsive pattern recognition receptors, signal transduction, inflammation, and phagocytosis [ 13 ]. Recent studies have shown that Gal-3 plays important roles in inflammatory processes and immunity during fungal infections [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations